The effect of comic strip media on third-grade students’ writing story essay - Herlandita, Rohmadhani; Nuroh, Ermawati Zulikhatin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This study aims to determine the effect of comic strip media on the ability to write stories for third-grade students at a private Islamic school in Porong. This research uses quantitative research. sampling with non-probability techniques to obtain 1 class, namely class III, following the data taken by the researchers. The data collection technique used the test method to find out the results of writing essays using a pre-test and post-test to find out how much influence the use of comic strip media had on the ability to write essays. In this study, the pre-experimental design was used with the one-group pretest- posttest design. The population that became the object of this research was 20 third-grade students of a private Islamic school in Porong. Based on data analysis using the N-Gain formula, it shows that the average result of the pre-test is 67.7, and the average result of the post- test score is 85.55. Based on data processing from the Eta Squared test, it was 0.871 in the pre-test and 0.882 in the post-test. If t 0.14 indicates that this comic strip medium has a significant influence, the results of the paired sample pre-test sig. (2-tailed) in the study are.000, then the decision-making is following the t-test. If the value of sig. (2-tailed) is below 0.05, then there is an increase or a very significant effect on the research variables. Therefore, it can be concluded that the use of comic strip media on the ability to write stories by third-grade students greatly affects their writing ability of students.